Gejala Metalingual Dalam Geguritan Bhima Swarga Sebagai Refresentasi Tradisi Ngaben Di Bali Utara - Komang Wahyu Rustiani; I Gst Md Swastya Dharma Pradnyan (Jayapangus Press, 2020)
Geguritan Bhima Swarga become important to analyze since contains culture codes which represent supreme traditions as the culture reinforcement in the North Bali. This qualitative research used semiotic theory of Michael Riffaterre which focused on the Matrix, Model, and Variant. The data was collected by observation, interview, and documentation. The data was reduced and presented using formal method and inductive-deductive technique. The result of the research reveals that metalingual aspects in geguritan are a sign which represents ngaben tradition in the North Bali. One of the examples is the word mangkata, which means lexically ‘raised’ or ‘awaked’. According to the variant in Balinese language, especially the North Balinese language, the word mangata has synonym to nangiang, nangun, ngangkasang which means ‘awake further’. The matrix, furthermore, can be discoursed as the effort of dedication sincerely to pull parent’s soul miseries out by doing the ritual ceremony. In short, it can be interpreted that the relation between Matrix, Model, and Variant shows that the word mangkata get symptom of metalanguage function or social cultural contextually is dedication ritual toward parent who already dead, which is known in Bali as the term ngaben.